DESIGN SOFTWARE REQUIREMENT SPECIFICATION THE SEHAT.ID APPLICATION SOFTWARE - Wahyu Hidayat; Farid Sukmana (JoEICT (Jurnal of Education And ICT), 2023)
This article discusses the design and development of the Sehat.ID application software which aims to provide holistic health benefits for users with a variety of features and services. This application allows users to monitor health conditions, carry out online medical consultations, access trusted health information, and get mental health support. Apart from that, this article also discusses the limitations of the Sehat.ID health application, such as medical regulations, data privacy and technical limitations. With the Sehat.ID application, it is hoped that users can easily access health information and get solutions that suit their needs. This article can be a reference for software developers and health application users.